ENVIRONMENTAL SUSTAINABILITY AND ECONOMIC DEVELOPMENT: A STUDY (International Journal of Food and Nutritional Sciences, 2021)
The aim of this paper is to study the environmental sustainability and economicdevelopment. Economic development is vital for enhancing living standards, drivingtechnological progress, and alleviating poverty. However, traditional development modelsoften exert significant pressure on natural resources and ecosystems, leading to issues suchas resource depletion, pollution, and biodiversity loss. Environmental sustainability, on theother hand, emphasizes the responsible management of natural resources and ecosystems toensure their availability for future generations. The challenge lies in balancing these twoobjectives to achieve long-term prosperity and ecological stability. Sustainable developmentaims to integrate economic growth with environmental stewardship. This involves promotingrenewable energy sources, implementing sustainable agriculture and forestry practices,adopting a circular economy model, and investing in green infrastructure.